Physiological intermolecular modification spectroscopy for the prediction of response to anti-tumor necrosis factor therapy in patients with inflammatory bowel diseases - Eftekhari, Pierre; Glaubitz, Lisa; Breidert, Matthias; Neurath, Markus; Atreya, Raja (Digestive Diseases, 2014)
Anti-tumor necrosis factor (TNF) antibodies have clinical efficiency only in a subgroup of patients with inflammatory bowel diseases (IBD). Prediction of clinical response is a critical clinical problem. Physiological intermolecular modification spectroscopy (PIMS) is a label-free technology performed in physiological conditions. PIMS enables real-time monitoring of dynamic molecular resonance of entire proteins and macromolecules of an individual. The aim of this study was to explore the capacity of PIMS to discriminate IBD patients regarding response to anti-TNF treatment.Protein extracts of peripheral blood mononuclear cells (PBMC) from 30 outpatients diagnosed with ulcerative colitis (UC) or Crohn's disease (CD) and treated with infliximab were subjected to PIMS analysis in a blinded transversal study. Total protein from each patient's PBMCs was challenged with infliximab. Dynamic changes in macromolecular interaction were registered while the temperature rose from -37 to 37°C. Individual macromolecular volume and molecular elasticity were determined for each patient.Clinical data revealed that 67% of UC and 79% of CD patients responded to infliximab therapy during the 3-month study period based on their respective clinical activity score. These results confirm that PIMS data predicted response to anti-TNF therapy with an accuracy of 96%.PIMS stratified IBD patients into two groups, responders and nonresponders, which correlated with the clinical efficacy of anti-TNF therapy. PIMS seems to be a powerful technology to adapt IBD treatment to the individual patient. Further studies with PIMS might enable to predict clinical response to biological treatment in IBD patients before the therapy is initiated.
EVALuna2:1885